Legitimacy Steps Delaying the A2024 Election Implementation - Junaedi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The legitimacy of the postponement of the 2024 General Election can be implemented, even if it is against the state constitution, including Amendments to the 1945 Constitution, Presidential Decrees, and constitutional conventions. The last way to postpone the election is by creating a constitutional convention. Changes are not made to the text of the Constitution, the Constitution. 45, but it is carried out in the practice of state administration, and it is challenging to create a constitutional convention on postponing elections. Moreover, ordinary people will readily perceive it as a 'deviation' from the 1945 Constitution.